Effect of Decellularized Amniotic Membrane on the Tendon–Bone Integration in Rotator Cuff Repair: A Comparative Rat Model Study - Jiangtao Wang; Chunbao Li; Jiating Zhang; Mingyang An; Gang Zhao; Samuel D. Stark; Yujie Liu (Orthopaedic Surgery)
ABSTRACT Objective Rotator cuff retear after arthroscopy repair is a difficult complication that is often due to poor tendon–bone healing. Decellularized amniotic membrane (DAM) has a variety of bioactive substances which have great potential to enhance tendon–bone healing. However, DAM has three layers, of which the middle basement layer is dense and thick. Whether DAM will hinder tendon–bone healing of rotator cuff after surgical repair is unclear. Our study aims to investigate the effect of DAM on tendon–bone healing of the rotator cuff after surgical repair. Methods Thirty‐three Sprague–Dawley (SD) rats were selected to establish unilateral supraspinatus (ST) tear models and were randomly treated with only suturing repair (OSR group, n = 11), and suturing repair with DAM placed between the ST and bone (DAM group, n = 11). In the normal control group (NCT group, n = 11), the supraspinatus was only exposed but not detached or repaired. After 4 weeks the rats were sacrificed. The assessment of specimens was conducted by micro‐CT analysis, histopathological evaluation, and biomechanical testing. Results The DAM group had a significantly higher ultimate load to failure, new bone volume, and histological evaluation at 4 weeks after surgery than the OSR group. When comparing the DAM group to the NCT group, the DAM group performed slightly worse in biomechanical testing, micro‐CT analysis, and histological evaluation. Conclusion When placed between tendon and bone at the rotator cuff footprint, DAM, despite its dense and thick basement layer, does not impede tendon–bone healing after surgical repair for rotator cuff injury, but rather promotes increased healing quality and biomechanical properties. However, the healing quality and biomechanical properties are still lower than that of the normal rotator cuff, and further improvement should be made to the application strategy of a DAM.